ELECTORAL REFORMS AND INTEGRITY: IMPACT ON UNIVERSAL ELECTIONS IN INDIA (International Journal of Food and Nutritional Sciences, 2021)
Electoral reforms in India have been an ongoing process aimed at enhancing the integrity, transparency, and inclusiveness of the election system. The country’s vast demographic diversity and complex political landscape necessitate continuous improvements to ensure the legitimacy of its electoral processes. This article examines the impact of electoral reforms on the integrity of universal elections in India, focusing on their role in promoting free, fair, and inclusive elections. By analyzing the historical context of electoral reforms, the challenges faced by the Election Commission of India, and the implementation of key reforms such as voter identification, electronic voting systems, and the strengthening of political party regulations, this research aims to highlight the improvements as well as ongoing issues. Additionally, the article discusses the role of electoral integrity in fostering public trust and ensuring the representative nature of India’s democracy.